(untitled) (International Journal of Environmental Sciences, 2025)
Background:Chronic kidney disease (CKD) is associated with accelerated atherosclerosis, even in younger populations. Traditional markers often fail to detect subclinical vascular changes early. This study evaluated the role of carotid and femoral intima-media thickness (cIMT, fIMT) as non-invasive markers of preclinical atherosclerosis in adolescent and young adult CKD patients. Methods:A prospective observational study was conducted involving 50 participants (25 CKD patients and 25 age- and sex-matched controls). Demographic, clinical, and biochemical parameters were recorded. B-mode ultrasonography was used to assess cIMT and fIMT bilaterally. Data were analyzed using t-tests, Pearson correlation, and multivariate regression. Results:CKD patients exhibited significantly higher cIMT (0.69 ± 0.06 mm) and fIMT (0.78 ± 0.07 mm) compared to controls (p<0.001). IMT correlated positively with serum creatinine, LDL, and triglycerides and negatively with eGFR. Multivariate regression identified serum creatinine and LDL as independent predictors of increased IMT. Conclusion:Increased cIMT and fIMT in young CKD patients reflect early vascular remodeling. Ultrasonographic IMT measurement is a sensitive and practical tool for early cardiovascular risk assessment in this vulnerable group.